In vivo characterization of a podocyte-expressed short podocin isoform - Linus Butt; David Unnersjö-Jess; Dervla Reilly; Robert Hahnfeldt; Markus M. Rinschen; Katarzyna Bozek; Bernhard Schermer; Thomas Benzing; Martin Höhne (BMC Nephrology, 2023)
Abstract The most common genetic causes of steroid-resistant nephrotic syndrome (SRNS) are mutations in the NPHS2 gene, which encodes the cholesterol-binding, lipid-raft associated protein podocin. Mass spectrometry and cDNA sequencing revealed the existence of a second shorter isoform in the human kidney in addition to the well-studied canonical full-length protein. Distinct subcellular localization of the shorter isoform that lacks part of the conserved PHB domain suggested a physiological role. Here, we analyzed whether this protein can substitute for the canonical full-length protein. The short isoform of podocin is not found in other organisms except humans. We therefore analysed a mouse line expressing the equivalent podocin isoform (podocin Δexon5 ) by CRISPR/Cas-mediated genome editing. We characterized the phenotype of these mice expressing podocinΔexon5 and used targeted mass spectrometry and qPCR to compare protein and mRNA levels of podocinwildtype and podocinΔexon5. After immunolabeling slit diaphragm components, STED microscopy was applied to visualize alterations of the podocytes’ foot process morphology. Mice homozygous for podocin Δexon5 were born heavily albuminuric and did not survive past the first 24 h after birth. Targeted mass spectrometry revealed massively decreased protein levels of podocinΔexon5, whereas mRNA abundance was not different from the canonical form of podocin. STED microscopy revealed the complete absence of podocin at the podocytes’ slit diaphragm and severe morphological alterations of podocyte foot processes. Mice heterozygous for podocin Δexon5 were phenotypically and morphologically unaffected despite decreased podocin and nephrin protein levels. The murine equivalent to the human short isoform of podocin cannot stabilize the lipid-protein complex at the podocyte slit diaphragm. Reduction of podocin levels at the site of the slit diaphragm complex has a detrimental effect on podocyte function and morphology. It is associated with decreased protein abundance of nephrin, the central component of the filtration-slit forming slit diaphragm protein complex.